Age Differences in Prefontal Recruitment During Verbal Working Memory Maintenance Depend on Memory Load - Cappell, K.A. (2009)
Positron emission tomography (PET) and functional magnetic resonance imaging (fMRI) studies have revealed age-related under-activation, where older adults show less regional brain activation compared to younger adults, as well as age-related over-activation, where older adults show greater activation compared to younger adults. These differences have been found across multiple task domains, including verbal working memory (WM). Curiously, both under-activation and over-activation of dorsolateral prefrontal cortex (DLPFC) have been found for older adults in verbal WM tasks. Here, we use event-related fMRI to test the hypothesis that age-related differences in activation depend on memory load (the number of items that must be maintained). Our predictions about the recruitment of prefrontal executive processes are based on the Compensation Related Utilization of Neural Circuits Hypothesis (CRUNCH; Reuter-Lorenz and Cappell, 2008). According to this hypothesis, more neural resources are engaged by older brains to accomplish computational goals completed with fewer resources by younger brains. Therefore, seniors are more likely than young adults to show over-activations at lower memory loads, and under-activations at higher memory loads. Consistent with these predictions, in right DLPFC, we observed age-related over-activation with lower memory loads despite equivalent performance accuracy across age groups. In contrast, with the highest memory load, older adults were significantly less accurate and showed less DLPFC activation compared to their younger counterparts. These results are considered in relation to previous reports of activation-performance relations using similar tasks, and are found to support the viability of CRUNCH as an account of age-related compensation and its potential costs.